An Image Resizing Function Embedded in an Inverse Discrete Cosine Transform - Sinchai, Ananta; Tuwanut, Panwit (My University, 2022)
Image resizing is an everyday activity and can be done in either a spatial domain or a transform domain. This work realizes that an image is commonly stored in the transform domain and the transformed image must be converted back to the spatial domain to display. This work hence proposes embedding an image resizing function based on a scaled frequency (SF) in a matrix operation of inverse discrete cosine transform (IDCT) for the sake of convenience. By adopting the proposed technique called as the SF-IDCT is not only capable of resizing the transformed image to a given resolution, but also acquiring the IDCT as a by-product. Image data can be shortened or lengthened in proportion to their frequencies by varying the frequencies of the DCT basis functions. Besides, the effects of modifying the pattern of the image data are also studied. The experimental results indicate that the SF-IDCT functions well. The proposed technique reconstructs an upsized image of equal or better visual quality than those produced by existing methods. For a downsized image, the performance of the presented approach is competitive with other available methods.
Keywords: Compressed domain technique; DCT; Image resizing; Image scaling; Inverse DCT